Pulp Responsiveness of Healthy Non-Pathological Teeth Following Surgical Enucleation of Cysts - Syed Nabil; Muhd Fazlynizam Rashdi; Abd Jabar Nazimi (Dentistry Journal)
Background/Objectives: Odontogenic cysts are pathological cavities lined by cells arising from odontogenic epithelial cells, occurring mostly on the tooth-bearing areas of the jaws. It is common to find that the apices of the teeth around the cyst are within the cyst’s cavities due to its expansion. This study aims to assess the outcome of cyst enucleation on the associated teeth, specifically the latter’s responsiveness after cyst enucleation. Methods: This retrospective study examined a sample of patients who had been previously treated for odontogenic cysts from 1 January 2000 to 31 December 2021. A list of patients was obtained and included whether they met the imposed inclusion criteria. The data collected included the patients’ preoperative and postoperative electric pulp testing readings and their timings. Results: In total, 77 individual teeth from 19 patients were included after meeting the inclusion/exclusion criteria. Overall, 57 out of the 77 (74%) teeth were responsive following long-term follow-up. Among the 57 teeth with a positive response, 8 teeth were initially non-responsive and regained their responsiveness after a period of time. Pulp responsiveness recovery was seen even 300 days after surgery. Conclusions: It is not certain that a tooth with apices involved in a cyst cavity will be non-vital following enucleation. It is recommended that these teeth be reassessed for a minimum of 10 months postoperatively before proceeding with root canal treatment.